Optical tomography system using microprocessor and ethernet - Ruzairi, Abdul Rahim; Goh, Chiew Loon; Chan, Kok San; Pang, Jon Fea; Leong, Lai Chan; Mohd Hafiz, Fazalul Rahiman (Emerald Group Publishing Limited, 2010)
Link to publisher's homepage at http://www.emeraldinsight.com/